Critical Engagements in Cultural Studies and Comparative Literature : Salvaging the Ruins of Empire - Juan, E. San (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
Few readers know how the U.S.-Marcos dictatorship in the Philippines inflicted torture and death with impunity on millions. Citizens became desaparesidos , to use the Latin-American term. In the Philippines, the victims were "salvaged," kidnapped and killed. This semantic change epitomizes the experience of colonized/neocolonized subjects since the bloody pacification of the islands in the 1899-1913 Filipino-American War. The usual meaning of "salvage," as rescue of selected relics from history's slaughterhouse, is restored here. In Critical Engagements in Cultural Studies and Comparative Literature: Salvaging the Ruins of Empire E. San Juan, Jr. reviews the dialectical process in postmodern art and symbolic expressions of the Cold War and analyzes the contradictions of re-neoliberal globalization and the retooled "salvaging" in the Duterte-Marcos' regime today. Neocolonialism and decolonization mutually inform the discussion of Filipino indigenization with the emergence of sikolohiyang Filipino -an original construction.